The Understanding of Hadith Sadaqah and Its Implementation on Social Empowerment: A Research on Jum’ah Berkah Tradition in Wonogiri Society - Kesturi, Ganis; Helmy, Muhammad Irfan (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
Gerdu is one of the neighborhoods located in the middle of the Wonogiri sub-district, Wonogiri Regency. Wonogiri has the title as the city of 'abangan'. However, the Gerdu community is enthusiastic in carrying out almsgiving activities on Friday blessing. This raises the question of how the community's understanding is related to the alms hadith (Hadith Sadaqah) and the community's motivations in carrying out almsgiving activities on Friday blessing. This research is a qualitative research using a phenomenological approach. Data analysis technique went through three stages, namely orientation, reduction and selection. The result of this study is that the understanding and implementation of the Gerdu community in the Wonogiri sub-district is carried out correctly and is in accordance with the Hadith. The Gerdu community in Wonogiri sub-district interprets alms as an activity to share their assets with families and people in need. The Gerdu community of Wonogiri sub-district already knows that the law of alms is a sunnah to be implemented, but for the Gerdu community of Wonogiri sub-district who are already accustomed to giving alms, they feel themselves obliged to give alms. While the implementation of the sadaqah hadith in the form of food alms in almsgiving activities on Friday blessings. As for the motivation of the Gerdu community in Wonogiri sub-district, there are two motivations, namely internal motivation and external motivation. The internal motivation is that there is a feeling of happiness when giving alms, a feeling of being stuck when not giving alms, people's beliefs about alms bringing sustenance, giving charity for da'wah bil hal. External motivation includes the availability of property owned, motivated from others, wanting to achieve husnul khotimah, understanding the true nature of property, and making it easier in all affairs.